Cultural Competency Training in Dental and Medical Education: Enhancing Communication and Patient-Centered Care: Cultural Competency in Healthcare Education - Khan, Yasar Alam; Ahmad, Shabir; Muhammad, Gul; Ahmed, Muneer; Saif, Iman; Waqar, Zubia; Ali, Muhammad Akram (Pakistan Journal of Health Sciences, 2024)
Competence is a core value of healthcare curriculum having a direct effect on the healthcare quality and patient health. Objective: To assess the effects and issues of integrated cultural competency education in dental as well as medical school curricula in order to improve critical and effective patient-centered care and cultural diversity in health care provision. Methods: According to PRISMA 2020 guidelines, electronic databases from PubMed, ScienceDirect, and Google Scholar were searched systematically for articles from the year 2016 to 2024. This involved studies that compared analysis of cultural competency incorporation into curricula, effects on health care provision, and the problems that confront trainers. Initially we identified 134 articles for consideration, 56 of which met the inclusion criteria, and 24 of which were reviewed with greater attention to program design, outcomes of training, and factors inhibiting implementation. Results: This review was able to demonstrate the increased student communication skills, patient and provider relations, as well as patient satisfaction. Nonetheless, the implementation challenges were seen in the following; Inconsistent curriculum frameworks; Faculty preparedness; and lack of support for training were cited as barriers to effective training. Gaps in implementing cultural competency interventions across the world were also pointed out. Conclusions: Cultural competence appeared to be an important approach in reducing the disparities in health and in healthcare provision. Suboptimal national dissemination indicated the necessity of high-fidelity curriculum structures, selective content focus, and sound institutional support to address the implementation barriers.